Decoction regulating phytochemicals' micromorphology changes and anti-inflammation activity enhancements originated from herb medicine supermolecules - Luping Yang; Xiang Zhang; Zhijia Wang; Xiaoyu Lin; Yaozhi Zhang; Jihui Lu; Linying Wu; Shuchang Yao; Wenguang Jing; Xuemei Huang; Penglong Wang (BMC, 2024)
Abstract Background Mahuang Fuzi decoction (MGF) is composed of three herb medicines that has been clinically used to treat inflammatory diseases for a long history. At present, more and more active phytochemicals' aggregations have been found during the thermodynamic process of herb medicine decoction, and revealing the clinical efficacy of herb medicine through supramolecular strategies is the focus of current research. However, it is not clear whether decoction induced supermolecules' morphological changes to modify activity. Methods Dynamic light scattering (DLS) and field emission scanning electron microscopy (FESEM) were used to analyze the micromorphology of MGF, MGF SA (MGF supermolecules), and MIX (physical mixture of MGF single decoction). The interaction and thermodynamic parameters of single herbs in a decoction were investigated by Isothermal titration calorimetry (ITC). The phytochemicals were systematically analyzed by ultra high performance liquid chromatography-Q Exactive hybrid quadrupole-orbitrap high-resolution accurate mass spectrometry (UHPLC-Q-Orbitrap HRMS). Under the safe dose on RAW264.7 cells, NO, IL-6 and TNF-α were determined by Enzyme-Linked ImmunoSorbent Assay (ELISA) method. NF-κB p65 translocation from the cytoplasm into the nucleus was examined using the immunofluorescence assay and the western blot, respectively. Furthermore, Metabolomics was used to discover potential biomarkers and the associated metabolic pathways of MGF SA treatment. Results There were nanoscale aggregations in MGF, and the micromorphology of the extracted MGF SA consisted of uniform particles; while the MIX micromorphology had no uniformity. ITC showed that the interaction MH-GC and FZ-GC were a spontaneous exothermic reaction, indicating that their phytochemicals had the property of self-assembly. Though the micromorphology between MGF, MGF SA, and MIX was obviously different, UHPLC-Q-Orbitrap HRMS results displayed that the main phytochemicals of MGF and MIX had nearly the same components. Interestingly, MGF and MGF SA could significantly inhibit the production of NO, and had better inhibition effect on the expression of nuclear protein NF-κB p65 than MIX, among which MGF SA had the best effect. Further investigation indicated that the perturbance of metabolic profiling in RAW264.7 inflammatory cells was obviously reversed by MGF SA. Conclusions The decoction enriched the key active phytochemicals and regulated the formation of homogeneous nanoparticles in MGF SA. The supermolecules in MGF SA significantly enhanced its anti-inflammatory activity, primarily affecting the NF-κB signaling pathway and the biosynthesis and metabolism of arginine in RAW264.7 inflammatory cells. Current study displayed that co-decocting herbal medicine were beneficial to the treatment of diseases than the mixture of the single herbs' extraction. Graphical Abstract